The Politics of Revitalising Agriculture in Kenya. (September 2014) - Poulton, Colin; Kanyinga, Karuti
<x xml:space="preserve">Abstract</x> In March 2004 the Kenyan government set out its Strategy for Revitalising Agriculture (SRA). Eight years later, almost no progress had been made. The SRA experience highlights both the potential and the limitations of competitive politics in promoting reform and the collective‐action challenge that can confront reform of agriculture‐sector institutions. The December 2002 election had created a window of opportunity for issue‐ and performance‐based politics in Kenya. However, the new government coalition began to unravel soon after attaining power, and the return to ethnically‐based patronage politics – illustrated here in relation to agriculture – undermined the SRA's chances of success.